A changeless land continuity and change in Philippine politics - Timberman, David G. (ISEAS–Yusof Ishak Institute, 2018)
This book examines the elements of continuity and change in Philippine politics and government over the last quarter century. This period, from the early 1960s through 1988, encompasses three distinct phases: the decline of “traditional” élite democracy, the imposition of martial law and “constitutional authoritarianism” under Ferdinand Marcos, and, most recently, the restoration of democracy under Corazon Aquino. By examining the elements of continuity and change during this period, this study attempts to provide a context for understanding current and future political developments in the Philippines.